Incidence of catheter-related urinary tract infections in a medical ward - Dória, Maria do Céu (2007)
Introduction and objectives: The indwelling urinary tract catheter (IUTC) is an important part of medical care. Up to 25% of patients admitted in hospitals are catheterized, of which, a high percentage are not justified. Catheter associated urinary tract infection (CAUTI) is the most common nosocomial infection documented, accounting for more than 40% of the total.Almost all patients admitted to an Internal Medicine ward in our hospital, pass through the Emergency Department, where they stay until there is a bed available. Therefore, a high number of patients have an IUTC at the time of medical ward admission. With this study we pretended to analyse the incidence of CAUTI in patients catheterized after hospital admission. Material and methods: Over a seven month time period, all the patients admitted to the medical ward with an IUTC, were included in the study. The urinary catheter was left in situ in those who had a clear indication. If no need for catheterisation was found, a urine sample was collected for culture, and the IUTC removed. Patients admitted with the diagnosis of urinary tract infection were excluded.In the study population we studied the motive stated for catheterization, the sex/age distribution, the percentage of positive urine cultures and the pathogens involved. Results: During this study, 15% (n=60) of the admitted patients had an IUTC. The reason stated for catheterization was to measure urinary output in 66.7% of the patients, urinary retention in 10% and no justification determined in 21.7% of the cases. In the studied population 93.3% (n=56) had no indication to maintain the IUTC. The results of the urine culture performed in these patients were positive in 23.2% (n=13), all with a IUTC in place for more than 3 days. Of those who had a negative urine culture result (n=40), 65% had already been medicated with a broad spectrum antibiotic for more then 48 hours; this fact could underestimate the number of CAUTI.